Significance of Diabetes (Siphon) in General And Orthodontic Treatment – A Literature Review - Vijayarangam, Kumaran; Pringle, Jebilla; Prasad, Vignesh; Suresh, Saravanan (Journal of Orofacial Research, 2019)
Diabetes Mellitus is a metabolic disorder of carbohydrate, protein and fat resulting from defective synthesis of insulin or its action on body tissue. It is one of the most commonly affected diseases worldwide and India has increasing prevalence in 2018 from 45% to 64%. Some of the deleterious effects of diabetes on oral health include xerostomia, debris accumulation, dental caries, recurrent infections, periodontitis etc. Periodontal destruction is the limiting factor in the orthodontic treatment. Maintaining oral hygiene and prevention of periodontal destruction is important before seeking for orthodontic treatment. Many researches and advancements made for periodontally compromised patients which include low profile brackets, copper NiTi wires and additional anchorages like mini screws. This article emphasizes on significance of diabetes in general and in orthodontic patients and treatment modalities of such patients.